Systematic Methodology for Estimating the Social Dimension of Construction Projects—Assessing Health and Safety Risks Based on Project Budget Analysis - María D. Alba-Rodríguez; Valeriano Lucas-Ruiz; Madelyn Marrero (Buildings)
One of the major challenges in the construction sector involves achieving sustainability in all three of its dimensions: economic, social, and environmental. Economic and environmental assessments have already been unified, but social indicators are still excluded. In this line, it is important for a rapid introduction of sustainability indicators that the evaluations of its three dimensions are carried out simultaneously and without adding new training or a large workload to the project. In this work, it is proposed to use the definition of tasks in construction cost databases. These, due to their long tradition in the sector, have a clear definition of the contours of the problem and the inventory of resources. Therefore, based on this inventory that does not leave any unaccounted element, the evaluation of the social dimension is proposed through the use of the work units of the databases as an element of occupational risk assessment. The project cost and risk assessment are performed simultaneously in the construction of a social housing project in Andalusia, Spain. The costs of prevention measures represent 5% of the work units’ costs and reduce the risk indicator by 65%.